Characterization of Transcriptional Expression and Regulation of Carotenoid Cleavage Dioxygenase 4b in Grapes - Meng, Nan; Wei, Yi; Gao, Yuan; Yu, Keji; Cheng, Jing; Li, Xiang-Yi; Duan, Chang-Qing; Pan, Qiu-Hong (Frontiers in Plant Science, 2020)
Norisoprenoids are important aromatic volatiles contributing to the pleasant floral/fruity odor in grapes and wine. They are produced from carotenoids through the cleavage of carotenoid cleavage dioxygenases (CCDs). However, the underlying mechanisms regulating VvCCDs expression remain poorly understood. In this study, we showed that VvCCD4b expression was positively correlated with the accumulation of β-damascenone, β-ionone, 6-methyl-5-hepten-2-one, geranylacetone, dihydroedulan I, and total norisoprenoids in developing grapes in two vintages from two regions. VvCCD4b was found to be principally expressed in flowers, mature leaves, and berries. Abscisic acid strongly induced the expression of this gene. Additionally, the present study preliminarily indicated that the activity of the VvCCD4b promoter was dropped under 37ºC treatment and also responded to the illumination change. VvCCD4b was expressed in parallel with VvMADS4 in developing grape berries. The latter is a MADS family transcription factor and nucleus-localized protein that was captured by yeast one-hybrid. A dual-luciferase reporter assay in tobacco leaves revealed that VvMADS4 downregulated the activity of VvCCD4b promoter. VvMADS4 overexpression in grape calli and Vitis quinquangularis Rehd. leaves repressed the VvCCD4b expression. In summary, this work demonstrates that VvCCD4b expression is positively correlated with the accumulation of norisoprenoids, and VvMADS4 is a potential negative regulator of VvCCD4b. Our results provide a new perspective for understanding the regulation of VvCCD4b expression and norisoprenoid accumulation in grapes.